2017
DOI: 10.12816/0040604
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hepcidin, Ferritin and C-Reactive Protein in Hemodialysis Patients

Abstract: Objective: Uremia is a state of heightened inflammatory activation. This might have an impact on several parameters including those used in the management of anemia as ferritin, serum iron, transferrin saturation, C-reactive protein (CRP) and hepcidin levels. In spite of this complexity the existing data indicate that hepcidin has an advantage over ferritin in guiding treatment of anemia in patients with chronic kidney disease (CKD) as it directly reflects iron availability and the status of iron homeostasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…5,6 Most of the study subjects were men with a percentage of 67.5%, similar to studies by Toima, et al, Mercadel, et al, Elmenyawi, et al 5,6,7 Higher male prevalence than female could be infl uenced by numerous factors like hypertension, hyperglycemia, lifestyle, kidney structure and hormonal diff erences. 8 The mean age in this study was 50.23 ± 1.04 years old, similar to studies by Mercadel, et al, Toima, et al, 2010, Elmenyawi, et al 5,6,7 Aging process infl uenced CKD progression and lesser function was expected from older nephrons. 9 Mean hemoglobin result in this study was 10.74 g/dL with SE of 0.36.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…5,6 Most of the study subjects were men with a percentage of 67.5%, similar to studies by Toima, et al, Mercadel, et al, Elmenyawi, et al 5,6,7 Higher male prevalence than female could be infl uenced by numerous factors like hypertension, hyperglycemia, lifestyle, kidney structure and hormonal diff erences. 8 The mean age in this study was 50.23 ± 1.04 years old, similar to studies by Mercadel, et al, Toima, et al, 2010, Elmenyawi, et al 5,6,7 Aging process infl uenced CKD progression and lesser function was expected from older nephrons. 9 Mean hemoglobin result in this study was 10.74 g/dL with SE of 0.36.…”
Section: Discussionsupporting
confidence: 82%
“…In a study by Elmenyawi et al the most frequent CKD stage in the population was stage 3 with mean CRP level at 3.52 and 4.28 mg/L. 7 In the study of Toima et al and Rasheed et al the highest staging in the population was stage 5 and mean CRP levels were, 6.0 and 7.59 mg/L. 5,13 This study found that CRP level increased along with a decrease in eGFR, which were consistent with other studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This may be explained by the higher sample size than our study and that one of those studies (12) was done on haemodialysis patients with chronic hepatitis C virus. Otherwise, an insignificant positive weak correlation between serum levels of hepcidin and ferritin (15).…”
Section: Resultsmentioning
confidence: 96%
“…This could be attributed to the risk of inflammatory and infection processes during dialysis. However, patients with RRT were excluded from the current study [44].…”
Section: Resultsmentioning
confidence: 99%